Prevalence of tuberculosis and associations in patients with pulmonary sarcoidosis - Shivute, Rosalia Ree Ndikuhole (My University, 2021)
Background: The incidence of sarcoidosis in South Africa is unknown, however, the incidence in the northern hemisphere is estimated to be between 5-40 per 100 000 and over three times more common in individuals of African American descent. South Africa suffers from dual epidemics of both human immunodeficiency virus (HIV) and tuberculosis (TB), and the incidence of TB is about 450,000 cases annually with 73% co-infected with HIV. Sarcoidosis and TB may present similarly and consequently sarcoidosis is often misdiagnosed as TB. Objectives: To describe the HIV and TB treatment history as well as co-morbidities in this cohort of patients with sarcoidosis. Methods: A retrospective study of patients diagnosed with pulmonary sarcoidosis at Helen Joseph Hospital, Johannesburg during January 2012 to June 2019. Results: The study identified 46 patients with sarcoidosis. Thirty-four were female. Median age was 51.5 years. Five patients were HIV infected, and virologically suppressed on antiretroviral treatment. Thirteen patients (28.3%) where treated for TB, ten (77%) were started on TB therapy after their diagnosis of sarcoidosis. The most common comorbidities were gastroesophageal reflux disease (17%) and hypertension (17%). Most patients (87%) were treated with prednisone. Conclusion: Empiric treatment for TB prior to the diagnosis of sarcoidosis was uncommon. Once on immune therapy for sarcoidosis there was an increase of both empiric and microbiologically driven TB therapy which suggests a need for improved TB prevention strategies for these patients
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine, 2021